Pengaruh Promosi terhadap Peningkatan Pendapatan pada Wedding Organizer di Kecamatan Siabu Kabupaten Mandailing Natal - Khoirul Bahri; Andi Hakim; Vebri Sugiharto (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The aim of this research is to determine the effect of promotion on increasing income for wedding organizers in Siabu District, Mandailing Natal Regency. The type of research used is field research with quantitative descriptive methods. The population and sample in this research were 65 wedding organizer consumers in Siabu District, Mandailing Natal Regency. Data was collected through observation, questionnaires distributed to respondents on a Likert scale and interviews with wedding organizer owners in Siabu District, Mandailing Natal Litian Regency, as well as documentation. The data analysis technique uses a multiple linear regression model with the help of the SPSS version 21 program. The results of multiple linear regression analysis show that promotion has a significant effect on increasing income for wedding organizers in Siabu District, Mandailing Natal Regency with a calculated t value of 3,770 which is greater than t table 1,670 and a significance value of 0.000 <0.05. These results show that Ha is accepted and H0 is rejected, meaning that the promotion variable (X) has a positive and significant influence on income (Y), which can be seen t count > t table (3,770 > 1,670). This means that the promotion variable has a simultaneous effect on increasing income for wedding organizers in Siabu District, Mandailing Natal Regency.